PTU-138 Population-based Study Of Ethnicity And The Diagnosis Gap In Liver Disease. (9th June 2014) - Alazawi, W; Mathur, R; Abeysekera, K; Hull, S; Boomla, K; Robson, J; Foster, GR
Abstract : Introduction: Awareness of liver disease as a major cause of morbidity and mortality has led to an increase in liver function tests (LFTs) performed in primary care with abnormal results a common finding. However, we hypothesise that a large gap exists between numbers of patients with abnormal LFTs and those with recorded liver diagnoses. Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver injury. Metabolic syndrome, common in people from the Indian subcontinent, is an important risk factor for NAFLD. We hypothesise that NAFLD is more common among adults of South Asian ethnicities. Methods: In a cross-sectional study of 690, 683 adults, registered in co-terminus general practices in a region with high ethnic diversity, we extracted demographic information and clinical care data including LFTs in the previous two years, liver disease diagnoses and co-morbidites from the EMIS Web computerised medical records. The breakdown of age, gender, deprivation, BMI, smoking status, alcohol consumption, co-morbidities and cholesterol was described for the whole population and for the six main ethnic groups of Bangladeshi, Indian, Pakistani, White, African and Caribbean. STATA 12 was used to conduct multivariate logistic regression analyses. Results: LFTs were performed on 218, 032 patients, of whom 31, 627 had elevated serum transaminases. Testing varied by age, ethnicity and the presence of co-morbidities. The prevalence of abnormal LFTs was highest among Bangladeshis and independent risk factors for abnormal LFTs included male gender, alcohol consumption and elements of the metabolic syndrome. The most commonly recorded liver diagnosis was NAFLD, followed by chronic viral infection and alcoholic liver disease. 88.4% (n = 27, 985) of patients with abnormal LFTs did not have a coded liver diagnosis. The prevalence of recorded NAFLD was highest among patients of Bangladeshi ethnicity. In a multivariate analysis, independent risk factors for NAFLD included Bangladeshi ethnicity, diabetes, raised BMI, hypertension and hypercholesterolaemia. Conclusion: Abnormal LFTs are common in the population, but are under-investigated and often remain undiagnosed. Bangladeshi ethnicity is an important independent risk factor for NAFLD. Among the group of patients with abnormal LFTs and no recorded liver diagnosis, many will have a liver disease that is amenable to further management, which may prevent complications. There is a need for evidence-based guidelines for the investigation, referral and management of patients with abnormal liver tests in the community in order to ensure early identification of treatable disease. Disclosure of Interest: None Declared.